Ledeniki - Mrak, Irena (Geografski obzornik, 2004)
Glaciers are known to be important fresh water containers as well as they are crucial in shaping the Earth's landscape. One could follow the news on the global warming almost every day. The latest is being best noticeable in the extent of glaciers around the North and the South Pole as well as in the mountains. It is not yet clear whether the glaciers are going to melt completely in the near future (and therefore life would only be possible in high latitudes) or is the Earth going to "cool down" and aproach the new Ice Age?
Keywords: glaciologija; ledeniki; klimatske spremembe